Impact of Learning-Together-Model of Cooperative Learning on Performance and Retention of Upper Basic Science Students in Kabba Metropolis - ABIODUN, David Kolawole; DAODU, Joshua Rotimi; IBIEJEMITE, Blessing Abiola; SAMTANI, Suleiman Ayuba (Ilorin Journal of Education, 2023)
This study examined the impact of Learning-Together-Model of cooperative learning on performance and retention of upper basic science students in Kabba Metropolis, Kogi State. The study was guided by two objectives, two research questions and two research hypotheses. The study adopted quasi-experimental involving pre-test, post-test and post posttest control group design. The students in the experimental group were exposed to Learning-Together-Model of cooperative learning while students in the control group were exposed to conventional teaching method. A total of 1450 JSS II students constituted the target population out of which 134 students were randomly selected as sample for the study. The instrument used for data collection was Basic Science Performance Test (BSPT). The instrument was duly validated and the reliability coefficient was found to be 0.84. The research questions were answered using descriptive statistics while the hypotheses were tested at p≤0.05 level of significance using independent t-test. The findings of the study showed that students in the experimental group who were exposed to Learning-Together-Model of cooperative learning performed significantly better than those in the control group who were exposed to conventional teaching method. Based on the findings of the study, it was recommended among others that Basic Science teachers in Junior secondary schools should adopt Learning-Together-Model of cooperative learning in teaching Basic Science.